2023
DOI: 10.3390/solar3030023
|View full text |Cite
|
Sign up to set email alerts
|

Global Atlas of Marine Floating Solar PV Potential

Abstract: In this paper, we analyse 40 years of maximum wind speed and wave height data to identify potential sites for solar photovoltaic (PV) systems floating on seas and oceans. Maximum hourly wave height and wind speed data were segregated into 5 distinct categories. These categorisations were then combined at the nearest wind speed and wave height grid point for each sea location, generating a comprehensive wind–wave map via a geographic information system (GIS) visualisation. We find that regions around the equato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It was observed that the most suitable locations were the Indonesian archipelago and the Gulf of Guinea locations (30.000 km 2 ), which can produce approximately one million terawatt hours of energy per year. This highlights the potential of offshore FPV systems in the global energy transition [28].…”
Section: Introductionmentioning
confidence: 83%
“…It was observed that the most suitable locations were the Indonesian archipelago and the Gulf of Guinea locations (30.000 km 2 ), which can produce approximately one million terawatt hours of energy per year. This highlights the potential of offshore FPV systems in the global energy transition [28].…”
Section: Introductionmentioning
confidence: 83%
“…Technical data for the analysis was gathered through the measurement of energy yield from the Floating Solar PV system. To validate and enhance the findings, this measured data was compared with simulation results obtained from the Global Solar Atlas, utilizing an online simulation platform [6], [7]. The comparison between actual performance and simulated outcomes offers valuable insights into the accuracy and reliability of the Floating Solar PV system in the specific environmental conditions of Muara Nusa Dua reservoir.…”
Section: Methodsmentioning
confidence: 99%
“…space sharing means the rational use of space resources to improve the power generation per unit of marine area (Golroodbari et al, 2021). The integration of offshore floating PV plants and offshore wind plants is ideal (Silalahi and Blakers, 2023). The natural complementarity of them from summertime to wintertime is conducive to the relative stability of the current output.…”
Section: Figurementioning
confidence: 99%